2015
DOI: 10.1167/15.15.12
|View full text |Cite
|
Sign up to set email alerts
|

The effect of blur on cortical responses to global form and motion

Abstract: Global form and motion sensitivity undergo long development in childhood with motion sensitivity rather than form being impaired in a number of childhood disorders and both impaired in adult clinical populations. This suggests extended development and vulnerability of extrastriate cortical areas associated with global processing. However, in some developmental and clinical populations, it remains unclear to what extent impairments might reflect deficits at earlier stages of visual processing, such as reduced v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 57 publications
4
19
1
Order By: Relevance
“…This would suggest that the under sampling theory posited for other visual deficits in amblyopia 36,49 could be applicable to global motion and form processing as well. These deficits do not seem to be dependent on the visibility of stimuli as has been reported before for normal participants, 50 as the fellow eyes of strabismic amblyopes which had similar visual acuity to the normal eyes (independent t-test, t (20) ¼ 1.25, P > 0.05) also showed raised thresholds for both motion and form domains.…”
Section: Comparison Of the Global Motion And Form Deficits In Amblyopiasupporting
confidence: 75%
“…This would suggest that the under sampling theory posited for other visual deficits in amblyopia 36,49 could be applicable to global motion and form processing as well. These deficits do not seem to be dependent on the visibility of stimuli as has been reported before for normal participants, 50 as the fellow eyes of strabismic amblyopes which had similar visual acuity to the normal eyes (independent t-test, t (20) ¼ 1.25, P > 0.05) also showed raised thresholds for both motion and form domains.…”
Section: Comparison Of the Global Motion And Form Deficits In Amblyopiasupporting
confidence: 75%
“…However, the effects on global form, motion and biological motion perception were not uniform, suggesting that spatial limitations of scotopic vision are insufficient in explaining midand higher-level visual performance under low light. Comparing the results to data previously collected photopically but with stimuli which were blurred in order to reduce the available spatial information, (Burton et al, 2015), scotopic form perception was less impaired than by blur leading to similar overall reductions in spatial vision. This suggests that the level of sensitivity in low light is greater than expected given the spatial impairments.…”
Section: Discussionsupporting
confidence: 52%
“…To test the extent to which reductions in global form and motion thresholds under low light could be explained by reductions in contrast sensitivity and acuity alone, results were compared to data collected previously in 20 typically sighted participants with simulated low vision (Burton et al, 2015). These participants completed the same coherent form and motion tests used here, viewed through a diffuser acting as a low pass filter at different separations from the screen which introduced different levels of blur.…”
Section: Contrast Sensitivity Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some findings indicate that acuity limits performance in motion tasks that require the detection of small spatial displacements, e.g., in apparent motion tasks (Roudaia, Bennett, Sekuler, & Pilz, 2010). Congruently, it has been shown that visual blur, i.e., degraded high spatial frequency information, impairs motion discrimination (Burton et al, 2015). However, the detrimental effect seems only moderate in comparison with the massive threshold increase observed for form perception.…”
Section: Age-related Changes In Early Sensory Processingmentioning
confidence: 99%